Peluang Pendidikan dan Pelatihan (Diklat) Pegawai Perempuan di Pemerintah Daerah di Provinsi Bali - AAIN, Marhaeni; AA Ayu, Sriathi (PIRAMIDA; Vol 9, No. 1 Juli 2013, 2013)
Education and training is a very important activity to be implemented in order to improve the competence of civil servants. A regulation governing the education and training of civil servants is the Indonesian Government Regulation Number 101 Year 2000 on Education and Job Training for Civil Servants. Improving the competence of civil servants through education and training become important in the career advancement of civil servants, education and training is often a requirement to fill a particular position. If the opportunity to participate in different training among civil servants of men and women, it will create different competencies, and in the end there are different opportunities for certain positions. The purpose of the research was to examine the perceptions of female civil servants (PNS) of their opportunities to participate in Education and Training at the Provincial Government of Bali. Respondents in this study were female civil servant who has held echelon positions of echelon 4 to 2 in all Local Government of Regencies / City and Province of Bali, which numbered 310 people. Samples were taken with a random sampling method. Data were collected through interviews and in-depth interviews. Data analysis technique used is descriptive statistic that comes with a descriptive analysis. The results showed the majority of respondents (over 90%) of respondents have completed the Education and Training, both Leadership Education and Training , Functional, and Technical Education and Training. Respondents who have not followed Leadership Education and Training are civil servants who had served echelon 4, and immediately follow the Leadership Education and Training 4. Respondents perceive that the functional and technical Education and Training are directly benefitted and related to their duties as compared with Leadership Education and Training, and they also found that it is useful for their work. Based on the existing data and the opinions of respondents, it can be  seen that the higher the levels of leadership education and training the lower the chances of female civil servants to participate in the Leadership Education and Training, even for Leadership Education and Training I, the chance of female civil servants are very low. The suggestions that can be put forward that there should be a policy of affirmative action to follow the higher level of Leadership Education and Training , in order to achieve a higher equal opportunity to attend the Education and Training.
Keywords: education and training; opportunities; female civil servants